(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2012)
Protective effects of Fenugreek seeds (Trigonella foenum graecum L), added in the diet, upon oxidative stress and dysfunctions in kidney, thyroid and liver of alloxan-diabetic rats were investigated. In our study, the alloxan-induced diabetes triggered 1) increased levels of glucose, total cholesterol and triglycerides in blood, 2) increased activities of alkaline phosphatase and transaminases in blood, 3) increased levels of creatinine, urea and protein in blood, 4) a decreased level of TSH and an increased level of free thyroxin in plasma. In addition, an oxidative stress, evidenced by an increase of lipids peroxidation level and superoxide dismutase activity associated with a decrease of glutathione peroxidase and catalase activities in hepatic and renal tissues, was observed. When Fenugreek seeds powder (100g/kg) was added in the food for 30 days, all this parameters were significantly shifted to more normal values. In conclusion, fenugreek seeds powder displays beneficial effects upon hepatotoxicity, nephropathy, thyroid dysfunction and oxidative stress in alloxan-diabetic rats. This property could be attributed to the presence of antioxidant components, such as complex polysaccharides and phenolic acids, as confirmed by analyses.Â